How Non-Heteronormative Mothers Negotiate Meaning: Experiencing and Contextualizing “Invisibility” - Wojciechowska, Magdalena (Qualitative Sociology Review, 2020)
This article aims to shed light on how non-heteronormative mothers—whose child had been conceived via artificial insemination of one of them with the sperm of an anonymous donor— decode, experience, and make meaning of diverse (symbolic) dimensions of their social invisibility, as well as how their understandings of the category at hand have an impact on projecting and negotiating their roles as mothers (especially in case of those women who did not give birth to their children). Drawing on specific examples from the field, I analyze how—while acting within the context of anxiety exemplifying their non-existing legal status—non-heteronormative mothers construct the image of self against the backdrop of no ready-made role scripts available, as well as strive towards making oneself (socially) visible. The insights at hand are based on data collected during my six-year ethnographic study of planned non-heteronormative motherhood in Poland, where same-sex relationships are not legally recognized.